2017
DOI: 10.1111/jog.13350
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of c‐Src tyrosine kinase and its downstream targets in pre‐eclamptic placenta

Abstract: The c-Src/MAPK/NF-ĸB signaling pathway may contribute to the pathogenesis of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…RNA editing site was also localized within 3’UTR of CD99L2 , that is mostly expressed on leukocytes, endothelial cells and plays a role in extravasation of neutrophils under inflammatory conditions [77]. Selection and maturation of T-cells are regulated by both LCK proto-oncogene, Src family tyrosine kinase ( LCK ) and tyrosine kinases ( ZAP70 ), as key signaling molecules essential for lymphokine production [78,79], moreover, LCK affects trophoblast invasion and decidualization [80,81]. Our analysis revealed underexpression of ZAP70 (log2FC = −2.14) and LCK (log2FC = −2.13), what could have an impact on growth-retarded fetus.…”
Section: Discussionmentioning
confidence: 99%
“…RNA editing site was also localized within 3’UTR of CD99L2 , that is mostly expressed on leukocytes, endothelial cells and plays a role in extravasation of neutrophils under inflammatory conditions [77]. Selection and maturation of T-cells are regulated by both LCK proto-oncogene, Src family tyrosine kinase ( LCK ) and tyrosine kinases ( ZAP70 ), as key signaling molecules essential for lymphokine production [78,79], moreover, LCK affects trophoblast invasion and decidualization [80,81]. Our analysis revealed underexpression of ZAP70 (log2FC = −2.14) and LCK (log2FC = −2.13), what could have an impact on growth-retarded fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several reports have shown that c-myc expression was dysregulated in preeclamptic placentas versus normal third-trimester placentas [41,42]. NF-kB protein expression and NF-kB phosphorylation in placentas were decreased significantly in patients with preeclampsia compared with controls [43,44]. These findings suggest that the downregulation of myc and NF-kB might cause the increase in the expression of miR-29a in the placentas of patients with preeclampsia.…”
Section: Discussionmentioning
confidence: 89%
“…c-Src is a tyrosine kinase protein that regulates many intracellular processes such as cell growth, differentiation, and proliferation phosphorylating intracellular proteins. c-Src is expressed in most the human cells, and a dysfunction [1][2][3] in its activation is related to the onset of neoplastic progression [4][5][6][7][8][9]. Such a protein is formed by a myristoylated SH4 domain that anchors the kinase on the membrane surface, the Unique domain, the structural SH3 and SH2 domains and the kinase domain (KD), which contains the active site [10][11][12] (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The dephosphorylation of Tyr 527 triggers a conformational rearrangement leading to the open/active form, where the interaction between the C-terminal tail and the SH2 domain vanished. The successive autophosphorylation of Tyr 416 further stabilizes the active form [2,17]. Therefore, the conformational equilibrium between the active and inactive states is tightly regulated by different molecular interactions that are dependent on different input signals (Figure 1).…”
Section: Introductionmentioning
confidence: 99%